1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of two Isoforms of Isopentenyl‐Diphosphate Isomerase from Elicitor‐Treated Cinchona Robusta Cells

Abstract: In Cinchona robusta (Rubiaceae) cell suspension cultures, the activity of the enzyme isopentenyldiphosphate isomerase (isopentenyl-POP isomerase) is transiently induced after addition of a homogenate of the phytopathogenic fungus Phytophthora cinnamomi. The enzyme catalyses the interconversion of isopentenyl-POP and dimethylallyl diphosphate (dimethylallyl-POP) and may be involved in the biosynthesis of anthrayuinone phytoalexins that accumulate rapidly after elicitation of Cinchona cells. From elicitor-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 46 publications
(75 reference statements)
1
19
0
Order By: Relevance
“…2a). IPP isomerase was characterized in Taxus media , Tripterygium wilfordii (Tong et al 2016), Gossypium barbadense (Wang et al (Phillips et al 2008), Camptotheca acuminate (Pan et al 2008), Cinchona robusta (Ramos-Valdivia et al 1997) etc.…”
Section: Enzymes Of Methylerythritol 4-phosphate (Mep) Pathwaymentioning
confidence: 99%
“…2a). IPP isomerase was characterized in Taxus media , Tripterygium wilfordii (Tong et al 2016), Gossypium barbadense (Wang et al (Phillips et al 2008), Camptotheca acuminate (Pan et al 2008), Cinchona robusta (Ramos-Valdivia et al 1997) etc.…”
Section: Enzymes Of Methylerythritol 4-phosphate (Mep) Pathwaymentioning
confidence: 99%
“…1; Rios-Estepa et al, 2008); (2) competitive inhibition of PR by (+)-menthofuran (Rios-Estepa et al, 2008); and (3) competitive inhibition of isopentenyl-diphosphate isomerase (enzyme 8 in Fig. 1) by geranyl diphosphate (Ramos-Valdivia et al, 1997). In a recent publication (Rios-Estepa et al, 2008), we reported that the (+)-menthofuran concentration in secretory cells was roughly 400 mM when plants were grown under greenhouse conditions, which increased dramatically under low-light stress conditions.…”
Section: Posttranslational Regulation Of Pathway Fluxmentioning
confidence: 99%
“…Hence, IDI gene duplication is relatively recent on the scale of higher plant evolution, and there may be differences in IPP isomerase properties or localization among different plant lineages (Ramos-Valdivia et al, 1997a. For example, in Cinchona robusta cell cultures that produce anthraquinones requiring a DMAPP unit, two IDI proteins are known with different kinetic characteristics and patterns of occurrence (Ramos-Valdivia et al, 1997b). These results are in contrast with this study, in which it was shown that the two Arabidopsis proteins have no significant differences in kinetic properties but have different patterns of subcellular localization.…”
Section: The Properties and Localization Of Idi May Vary Among Plant mentioning
confidence: 99%